Fodor's 2009 Paris. (New York : Fodor's Travel, 2009)
A comprehensive travel guide to the city of Paris, that features information on accommodations and restaurants, festivals, entertainment and shopping, and interesting tourist sites; and includes a foldout map.
"Pullout map inside"--Cover.
Cover title: Paris 2009.
Includes index.
Young Adult
Keywords: Paris (France) -- Guidebooks; Paris (France) -- Guidebooks